Enhancing Reading Comprehension Through Strategic Reading Approaches Among Second Language Learners - R. Fathima Shirafa; M.J.F Sujani; M.R Rishad Muhammed; MB Nowzath (Amandemen: Journal of Learning, Teaching and Educational Studies, 2025)
This research investigates strategies to enhance reading comprehension among second language learners, specifically focusing on grade six students at KM/STR/ Muslim Madya Maha Vidyalaya. Many students struggle with reading comprehension, leading to low academic performance and a negative attitude toward English learning. The study aims to identify effective reading strategies that can improve students' understanding, motivation, and confidence in reading.A mixed-method approach was used, incorporating both qualitative and quantitative data collection. The research involved pre-tests, post-tests, questionnaires, mind-mapping activities, and observations. Findings revealed that students initially had limited knowledge of reading strategies and faced difficulties in understanding text meaning. However, after introducing seven specific reading strategies, students showed significant improvement in their ability to analyze texts, predict meanings, and develop critical thinking skills. The study highlights the importance of integrating structured reading strategies in teaching methodologies. Recommendations include using visualization techniques, audio formats, and interactive discussions to make reading a more engaging experience. The findings suggest that developing a habit of reading, increasing metacognition skills, and expanding knowledge of various genres can further enhance comprehension levels. Ultimately, this research contributes valuable insights into improving second-language reading education through targeted interventions.